Presence of the cotton spotted bollworm, Earias vittella (F.) (Lepidoptera Noctuidae), in East Africa. (Bollettino di zoologia agraria e bachicoltura, 2024)
The Cotton spotted bollworm Earias vittella (F.) was collected in the Gezira region of Sudan near Wad Medani. Larvae were found feeding on Okra fruits Hibiscus esculentus during November 1986.